Toward climate-smart agriculture in West Africa: a review of climate change impacts, adaptation strategies and policy developments for the livestock, fishery and crop production sectors - Zougmoré, Robert B.; Partey, Samuel T.; Ouédraogo, Mathieu; Omitoyin, Bamidele; Thomas, Timothy S.; Ayantunde, Augustine A.; Ericksen, Polly J.; Said, Mohammed Yahya; Jalloh, Abdulai (Springer, 2016)
Many projections of the impact of climate change on the crop, livestock and fishery production sectors of African agriculture are reported in the literature. However, they may be arguably too general to understand the magnitude of impact and to inform adaptation strategies and policy development efforts that are tailored to promoting climate- smart agriculture in the West African region alone. This paper was synthesized from several scholarly literature and aimed at providing up-to-date information on climate change impacts, adaptation strategies, policies and institu- tional mechanisms that each agriculture subsector had put in place in dealing with climate change and its related issues in West Africa. For each subsector (crop, fishery and livestock), the current status, climate change impacts, mitigation and adaption strategies have been analyzed. In addition, we reviewed recent policy initiatives in the region that foster the development and adoption of climate-smart agricultural options to improve resilience of farming systems and livelihoods of smallholder farmers to climate change risks. From community to national and regional levels, various strategies and policies are also being taken to guide actions and investment for climate-smart agriculture in West Africa.